Eﬀect of phosphorus, biofertilizers and zinc application on growth and quality- attributing characteristics of garden pea (Pisum sativum) - Mahendra Yadav; RS Meena; ARK Pathan; OP Garhwal (Current Horticulture, 2025)
A ﬁeld experiment was conducted during November 2021 to February 2022 and November 2022 to February 2023, comprising 32 treatment combinations replicated three times, at Rajasthan Agricultural Research Institute, Durgapura, Jaipur, Rajasthan. It followed a split plot design with main plots assigned to four phosphorus levels (P2O5 @ 0, 20, 40 and 60 kg/ha) and two biofertilizer conditions (without inoculation and with inoculation of Rhizobium + PSB). Sub-plots were dedicated to four zinc levels (control, 2.5, 5.0 and 7.5 kg Zn/ha). There was signiﬁcantly maximum plant height (65.17, 63.47 and 64.32 cm), number of primary branches (2.57, 2.45 and 2.51), minimum days to 50 % ﬂowering (41.90, 41.51 and 41.70), nitrogen content (3.74, 3.52 and 3.63 %) and protein content (23.40, 21.97 and 22.69 %) were recorded with application up to P2O5 40 kg/ha, In biofertilizer, maximum plant height (64.42, 63.03 and 63.72 cm), number of primary branches (2.61, 2.52 and 2.57), minimum days to 50 % ﬂowering (42.30, 42.82 and 42.56) nitrogen content (3.66, 3.39 and 3.53 %) and protein content (22.90, 21.20 and 22.05 %) were recorded with inoculation (Rhizobium+PSB) and In zinc treatments the maximum plant height (65.05, 64.06 and 64.56 cm) number of primary branches (2.58, 2.50 and 2.54) minimum days to 50 % ﬂowering (42.09, 41.25 and 41.67) nitrogen content (3.57, 3.39 and 3.48 %) and protein content (22.31, 21.19 and 21.75 %) were recorded with 5.0 kg Zn/ha, respectively.